Pengaruh Model Error Analysis Based Learning Terhadap Kemampuan Literasi Matematis Siswa Kelas VIII Berdasarkan Indikator OECD - Regina Maharani; Ketut Sarjana; Nilza Humaira Salsabila (Program Studi Pendidikan Matematika, FSTT, Universitas Pendidikan Mandalika, 2025)
This research aimed to determine the effect and the magnitude of the effect of the Error Analysis Based Learning model on the mathematical literacy ability of eighth-grade students at SMPN 13 Mataram during the 2025/2026 academic year. This research was a quasi experiment with a posttest only control group design. The population of this study was all 11 eighth-grade classes, totaling 426 students. The sample was selected using the cluster random sampling technique, resulting in two classes: class VIII-I as the control class with 38 students, which used Direct Instruction, and class VIII-F as the experimental class with 38 students, which used the Error Analysis Based Learning model. Data were collected through a mathematical literacy ability test and analyzed using normality and homogeneity tests. Based on the data analysis, the average mathematical literacy ability score of the experimental class students (81.71) was higher than that of the control class (51.75). The result of the Two-Tailed Independent Samples t-test showed a significance value (sig) of 0.000<0.05, meaning there was a significant difference in the average mathematical literacy ability scores between the control and experimental classes. The magnitude of the effect, calculated using the effect size formula, was 2.220, which indicates that the influence provided falls into the very high category. Therefore, it can be concluded that the Error Analysis Based Learning model has a significant effect on the mathematical literacy ability of eighth-grade students at SMPN 13 Mataram.